Herlyn-Werner-Wunderlich Syndrome in pregnancy - Novy Ngan; Erry Gumilar Dahlan; Eighty Mardiyan Kurniawati (Universitas Airlangga, 2019)
Objectives: To prevent Herlyn-Werner-Wunderlich syndrome’s complication in pregnancyCase Report: Presenting 2 cases pregnant with Herlyn-Werner Wunderlich syndrome, which is both of the case diagnosed at teenage and becoming pregnant then delivered by cesarean due to severe preeclampsia.Conclusion: High suspectious is needed to diagnose Herlyn-Werner-Wunderlich syndrome and early diagnosis is better prognosis. The gold standard diagnostic is MRI. The treatment is resection of the vaginal septum, drainage, and marsupialization. Preconception Counseling is important to prevent or to reduce the pregnancy complications.